Multiple tooth extractions in radiotherapy patients: indications, osteoradionecrosis risk and possible oral rehabilitation: case report - Bachesk, Andressa Bolognesi; Piacentini, Marcello; Libório, Ana Luiza de Moura; Farah, Gustavo Jacobucci; Pieralisi, Neli; Pavan, Ângelo José (Brazilian Dental Science, 2017)
Osteoradionecrosis (ORN) is one of the most severe oral complications after the head and neck cancer treatment. Tooth extraction, through its traumatic stimulation, is identified as an important predisposing factor. Indications and preventive methods for carrying out these procedures in irradiated patients are questioned, thus, establishing appropriate protocols is essential. This article reports a case of multiple tooth extractions in a cancer patient whose preventive measures were taken without the occurrence of complications. Based on a literature review, this paper accounts the appropriate indications of this procedure, the risk of developing osteoradionecrosis, and the prevention possibilities for this sequela. In addition, this report addresses a viable oral rehabilitation alternative after this kind of surgery by using overdenture on the lower jaw teeth.